Integration of Islamic Values and Psychology as a Strategy for Adolescent Mental Health Recovery in The Context of Social Media - Azizah, Khoridatul; Syafiqoh, Imro’atus (Fakultas Agama Islam Universitas Billfath, 2025)
This article aims to analyze a holistic strategy based on the integration of psychological approaches and Islamic values in addressing the negative impacts of social media on adolescent mental health. The intended strategy focuses on strengthening mental resilience through Islamic mindfulness combined with spiritual values such as tawakkal (trust in God), patience, gratitude, and dhikrullah (remembrance of God) as forms of spiritual coping. This study employed a qualitative, case-study approach with adolescents in Tlogoretno Village. The research subjects consisted of adolescents aged 15–18 who experienced anxiety, stress, depression, sleep disturbances, and tendencies toward social isolation due to social media use. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, display, and conclusion drawing. The findings indicate that Islamic mindfulness–based strategies effectively mitigate the negative impacts of social media, with greater effectiveness when combined with the practice of Islamic values. This study recommends a holistic intervention model comprising Islamic-based digital literacy, Islamic mindfulness practices, and strengthening supportive religious communities. These findings affirm that integrating psychology and Islamic values can strategically foster adolescent mental resilience in the digital era.